Antenatal maternal anxiety and stress and the neurobehavioural development of the fetus and child: links and possible mechanisms. A review - Van den Bergh, Bea R.H.; Mulder, Eduard J.H.; Mennes, Maarten; Glover, Vivette (Neuroscience and biobehavioral reviews, 2005)
A direct link between antenatal maternal mood and fetal behaviour, as observed by ultrasound from 27 to 28 weeks of gestation onwards, is well established. Moreover, 14 independent prospective studies have shown a link between antenatal maternal anxiety/stress and cognitive, behavioural, and emotional problems in the child. This link generally persisted after controlling for post-natal maternal mood and other relevant confounders in the pre- and post-natal periods. Although some inconsistencies remain, the results in general support a fetal programming hypothesis. Several gestational ages have been reported to be vulnerable to the long-term effects of antenatal anxiety/stress and different mechanisms are likely to operate at different stages. Possible underlying mechanisms are just starting to be explored. Cortisol appears to cross the placenta and thus may affect the fetus and disturb ongoing developmental processes. The development of the HPA-axis, limbic system, and the prefrontal cortex are likely to be affected by antenatal maternal stress and anxiety. The magnitude of the long-term effects of antenatal maternal anxiety/stress on the child is substantial. Programs to reduce maternal stress in pregnancy are therefore warranted.